Frontiers of evangelization: Indians in the Sierra Gorda and Chiquitos missions - Jackson, Robert H. (University of Oklahoma Press, 2017)
"Comparing the Franciscan missionary region of Sierra Gorda (Mexico) with the Jesuit missions of Chiquitos (Bolivia), Jackson argues that the two Catholic orders differed more in the organization of their missions and their role in the larger colonial system than in their methods of evangelization. The true point of difference between the two areas was whether or not their native groups were sedentary, as in the case of the Guaraní of Chiquitos, or non-sedentary, as were the Pames and Jonaces of the Sierra Gorda. Drawing upon his decades of archival research, Jackson concludes that non-sedentary populations were more prone to demographic collapse once they were brought into the mission system, whereas sedentary groups experienced more robust growth and were better able to weather mortality brought by disease or natural disaster"--Provided by publisher